Pengaruh Strategic Risk Management terhadap Kinerja Perusahaan melalui Praktik Corporate Governance: Studi PT Cengkareng Permai di Cengkareng, Jakarta Barat - Faizal Roni; Desri Yani; Suripah Suripah; Eva Marsusanti; Aliffah Kusumaningrum (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2026)
This study aims to analyze the effect of Strategic Risk Management on Firm Performance through Corporate Governance Practices at PT Cengkareng Permai. The study employed an explanatory quantitative approach using survey data collected from 100 employees selected through purposive sampling. Data were gathered using a closed-ended questionnaire based on a five-point Likert scale and analyzed using SEM-PLS with SmartPLS to examine direct and indirect relationships among the research variables. The findings indicate that Strategic Risk Management has a positive and significant effect on Corporate Governance Practices and Firm Performance. Corporate Governance Practices also have a positive and significant effect on Firm Performance and partially mediate the relationship between Strategic Risk Management and Firm Performance. These results suggest that effective risk identification, analysis, mitigation, reporting, and monitoring can improve company performance when supported by transparent, accountable, independent, responsible, and fair governance practices. The implication of this study is that companies should integrate strategic risk management with strong corporate governance to enhance adaptability, accountability, operational efficiency, and sustainable performance.